The impact of changes in land-use patterns and rainfall variability on range condition and pastoral livelihoods in the Borana rangelands of southern Oromia, Ethiopia - Madakadze, I.C. (Ignacio Casper) (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.